Nano-enzyme coating modified self-powered metal composite film and preparation and application thereof

By using a self-powered metal composite film modified with nanoenzyme coating on the surface of the titanium implant, the problem of unsatisfactory bone binding effect and insufficient antibacterial performance caused by inert surface of the titanium implant is solved, and the effect of improving the microenvironment of bone tissue and promoting bone repair and regeneration is achieved.

CN119499451APending Publication Date: 2025-02-25ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411718456.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Due to inertness on the surface of existing titanium implants, the bone binding effect is not ideal and the antibacterial performance is insufficient. The improvement of the bone microenvironment is ignored during the design and application process, which affects the healing speed and quality of bone defects.

Method used

A self-powered metal composite film modified with nanoenzyme coating is made of a titanium sheet covered with manganese dioxide nanocoated surface and a magnetostrictive material/polyvinylidene fluoride trifluoroethylene film after being combined and polarized. It has electroactive and catalytic activity, which can regulate the reactive oxygen concentration in bone tissue and improve the microenvironment of bone tissue.

Benefits of technology

By regulating the reactive oxygen concentration in bone tissue, improving the microenvironment of bone tissue, significantly improving the microenvironment quality of bone defects, promoting bone repair and regeneration, and improving the efficacy of bone implants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005157436730000011
    Figure HDA0005157436730000011
  • Figure HDA0005157436730000012
    Figure HDA0005157436730000012
  • Figure HDA0005157436730000013
    Figure HDA0005157436730000013
Patent Text Reader

Abstract

The invention discloses a self-powered metal composite film modified by a nano-enzyme coating as well as preparation and application of the self-powered metal composite film, and belongs to the field of material synthesis. The composite film is obtained by compounding a titanium sheet covered with a manganese dioxide nano-coating and an MSM / PVTF film and then carrying out polarization treatment on the compounded titanium sheet and the MSM / PVTF film. The composite film has a manganese dioxide nano-enzyme coating surface and a polarized MSM / PVTF surface, has biological activity and electroactivity capable of being regulated and controlled by an external field, can more efficiently catalyze and decompose hydrogen peroxide in a bone repair microenvironment, reduces oxidative stress, and improves the bone repair efficiency. An oxidative stress microenvironment with high active oxygen concentration is converted into an oxygen-enriched microenvironment with low active oxygen concentration, so that the microenvironment of a bone defect part can be remarkably improved, and the composite material can be used for repairing bone defects and promoting bone tissue repair and regeneration. The preparation method is simple, and the electrical properties and catalytic properties of the composite film can be regulated and controlled by adjusting the hydrothermal temperature, the hydrothermal time, the polarization field intensity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the biomedical field, and in particular to a self-powered metal composite film and a preparation method and application thereof. Background Art

[0002] With the increasing prevalence of traumatic fractures and degenerative bone and joint diseases, the use of orthopedic implants has also increased accordingly. Due to good machinability and excellent biocompatibility, medical metal titanium (Ti) and its alloys are the preferred materials for dental implants and hip arthroplasty, and are widely used in oral and orthopedic clinics. However, the surface of titanium implants is an inert surface, resulting in unsatisfactory bone bonding and insufficient antibacterial properties. In order to improve this situation, researchers have been exploring how to promote the bonding of titanium implants with bone tissue through material surface modification.

[0003] Domestic and foreign scholars have tried many physical and chemical methods to modify the surface of titanium and its alloys to improve surface activity. A series of methods and technologies that are now widely used include: mechanical surface treatment, absorbable sandblasting media treatment, titanium slurry coating surface treatment, hydroxyapatite coating and modification, large-particle sandblasting acid etching (SLA) treatment, etc. Most of these modifications are designed to change the surface morphology of the implant, hoping that the rough contact surface can increase the contact area between the bone and the implant, improve the bonding force of the implant-bone interface, and thus form a long-term and stable bone bond. However, there is a common problem in the current application of bone implants, that is, most of them ignore the improvement of the bone microenvironment during the design and application process. This results in the integration effect of the implant with the host bone being less than expected, affecting the healing speed and quality of the bone defect. Therefore, current research and development needs to pay more attention to how to improve the efficacy of bone implants by improving the bone tissue microenvironment.

[0004] The bone tissue microenvironment refers to the same microenvironment shared by various cells in the bone tissue, which plays an important role in the process of osteogenesis and bone repair. The bone microenvironment is a complex structure and biological system, which can be divided into three parts: physiological microenvironment, chemical microenvironment and physical microenvironment according to its function and the components it contains. Various factors in the microenvironment during bone injury, such as low oxygen tension and high reactive oxygen species (ROS) levels, will hinder bone healing at different levels. For example, in patients with osteoporosis, excessive activation of reactive oxygen species will destroy the formation of osteoblasts and hinder the differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteoblasts, thereby impairing bone healing. A large amount of evidence shows that the excessive ROS induced by hypoxia in the bone defect area has an important effect on delaying bone regeneration. Excessive production of reactive oxygen species (ROS) and insufficient antioxidant levels can cause oxidative stress, which can promote bone resorption under oxidative stress conditions: by inducing apoptosis of osteoblasts and osteocytes, promoting the generation and activation of osteoclasts, and thus increasing bone resorption. This imbalance can lead to bone diseases such as osteoporosis; in addition, high levels of reactive oxygen can inhibit the activity and differentiation of osteoblasts, hindering bone mineralization and bone formation. Moreover, excessive oxygen supplementation in a short period of time can cause high oxygen tension and affect the activity of osteoblast precursor cells, which can lead to a decrease in bone mass during bone remodeling. Therefore, it is crucial to reasonably restore the hypoxic state of the bone microenvironment to promote bone repair. The ideal implant surface should provide a good osteoinductive microenvironment for new bone formation, improve new bone formation and bone integration, and at the same time have good bone integration stability. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a self-powered metal composite film modified with a nanozyme coating and its preparation and application. The composite film has both electrical activity and catalytic activity, can regulate the concentration of reactive oxygen in bone tissue, improve the microenvironment of bone tissue, and is applied on the surface of metal implants, which has positive significance for bone repair.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect of the present invention, the present invention provides a composite film obtained by combining a titanium sheet with a manganese dioxide nano-coating on the surface and a magnetostrictive material / polyvinylidene fluoride trifluoroethylene (MSM / PVTF) film and then polarizing it.

[0008] In some specific examples of the present invention, the piezoelectric coefficient d of the composite film is 33 Satisfy: -23pC / N≤d 33 <0pC / N or 0pC / N<d 33 ≤23pC / N.

[0009] In some specific examples of the present invention, the thickness of the manganese dioxide nano-coating is 1 to 2 μm.

[0010] In some specific examples of the present invention, the thickness of the MSM / PVTF film is 35-70 μm.

[0011] In some specific examples of the present invention, the magnetostrictive material (MSM for short) is terbium dysprosium iron alloy or cobalt ferrite tetraoxide.

[0012] In some specific examples of the present invention, the manganese dioxide nano-coating is composed of manganese dioxide nano-sheets, and the size of the nano-sheets is 80-900 nm.

[0013] In some specific examples of the present invention, the manganese dioxide nano-coating is composed of manganese dioxide nano-sheets and manganese dioxide nano-rods, the size of the nano-sheets is 80-900 nm, and the size of the nano-rods is 1-4 μm.

[0014] In some specific examples of the present invention, the compounding is hot pressing compounding.

[0015] In a second aspect of the present invention, the present invention provides a method for preparing the composite film, comprising the following steps:

[0016] (1) preparing polyvinylidene fluoride trifluoroethylene and N,N-dimethylformamide into a polyvinylidene fluoride trifluoroethylene solution, adding a magnetostrictive material thereto, ultrasonicating for 3 to 9 hours, stirring for 2 to 4 hours, and obtaining a mixed solution; wherein the feeding ratio of the polyvinylidene fluoride trifluoroethylene, N,N-dimethylformamide and the magnetostrictive material is 1 g: (5 to 6) mL: (0.05 to 0.15) g; forming the mixed solution into a thin film by a coating method, and then heat treating at 180° C. to 240° C. for 0.5 to 2 hours, and obtaining an MSM / PVTF film after cooling;

[0017] (2) dissolving potassium permanganate and HCl in a molar ratio of 1:(39-41) in deionized water, stirring for 30 min-1 h to obtain a hydrothermal precursor solution, wherein the final concentration of potassium permanganate in the hydrothermal precursor solution is 0.3-0.4 mol / L; immersing a titanium sheet in a hydrothermal reactor containing the hydrothermal precursor solution, performing a hydrothermal reaction at 80-150° C. for 5-20 h, taking out and washing with deionized water several times to obtain a titanium sheet with a coating on the surface;

[0018] (3) hot pressing the MSM / PVTF film obtained in step (1) and the titanium sheet with the coating on the surface obtained in step (2) to obtain a composite titanium film, wherein the hot pressing temperature is 180 to 230° C. and the hot pressing time is 0.5 to 1.5 h;

[0019] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment to obtain the target product.

[0020] In some specific examples of the present invention, in step (1), the magnetostrictive material (MSM) is terbium dysprosium iron alloy powder or cobalt tetraoxide ferrite particles.

[0021] In some specific examples of the present invention, in step (4), the polarization treatment is contact polarization.

[0022] In some specific examples of the present invention, in step (4), the high voltage electric field intensity of the polarization treatment is 40 to 70 KV / mm, and the time of the polarization treatment is 2 to 10 min.

[0023] In some specific examples of the present invention, the thickness of the manganese dioxide nano-coating is 1 to 2 μm.

[0024] In some specific examples of the present invention, the thickness of the MSM / PVTF film is 35-70 μm.

[0025] In the third aspect of the present invention, the present invention provides applications of the composite film, especially in repairing bone defects, promoting bone tissue regeneration, reconstructing bioelectric microenvironment, etc.

[0026] The target product prepared by the present invention has both a manganese dioxide nano-coating surface and a polarized MSM / PVTF surface, and has both biological activity and electrical activity. On the one hand, the manganese dioxide nano-coating surface exhibits good biological activity and obvious nanoenzyme high-efficiency catalytic properties, which can catalytically decompose hydrogen peroxide (H2O2) in the bone repair microenvironment, remove reactive oxygen, reduce oxidative stress, and promote the generation of oxygen, converting the oxidative stress microenvironment with high reactive oxygen concentration into an oxygen-rich microenvironment with low reactive oxygen concentration, which helps to significantly improve the microenvironment of the bone defect site; moreover, the manganese dioxide nano-coating is a nanosheet or a mixture of nanosheets and nanorods, with a large specific surface area and uniform morphology. After being implanted in the bone damage area, the material surface contacts the bone tissue microenvironment, and the larger implant surface area improves the interaction with the bone tissue microenvironment. The surface potential of the MSM / PVTF film after polarization treatment makes the composite film self-powered, which can generate electrical signals under mechanical stress, and use the electrical signals on the surface of the material to change the cell microenvironment, promote the proliferation and differentiation of bone cells, and accelerate the bone tissue repair process. At the same time, the surface electrical activity of the MSM / PVTF film after polarization treatment can also be regulated by an external magnetic field; in addition, experiments show that the surface potential provided by the MSM / PVTF film after polarization treatment promotes the catalytic activity of the manganese dioxide nanocoating and can generate oxygen more quickly. This means that when the composite film is implanted in the body as an implant, its ability to interact with the microenvironment of human bone tissue can be regulated by changing the external magnetic field, thereby improving the efficiency and quality of bone tissue regeneration, especially in the repair of osteoporotic bone damage, which can effectively improve the efficiency of bone defect repair. External field regulation greatly facilitates the regulation of implants in the body. In addition to regulating the electrical activity by an external field, composite films with different surface potentials can be obtained by changing the polarization electric field during the preparation process, or by changing parameters such as the hydrothermal temperature and the hydrothermal time to adjust the surface physicochemical properties of the composite film to obtain different biological activities and electrical activities, thereby meeting different application requirements. It can be seen that the composite film of the present invention, which reshapes the material interface microenvironment using MSM / PVTF and MnO2 nano-coatings and is applied to the surface of metal implants, has significant advantages in bone repair, not only expanding the range of interaction between the material and bone tissue, but also further promoting the repair and regeneration of bone tissue by reducing the level of oxidative stress. The composite film of the present invention can be used to repair bone defects and improve the bioelectric microenvironment. It can be used in the biomedical field as a material for reconstructing the bioelectric microenvironment of bone defects, and shows great application potential in promoting bone tissue repair and regeneration.

[0027] Compared with the prior art, the present invention has the following beneficial technical effects:

[0028] The composite film of the present invention has both a manganese dioxide nanozyme coating surface and a polarized MSM / PVTF surface. It has both biological activity and electrical activity that can be regulated by an external magnetic field. The two produce a synergistic effect, which promotes more efficient catalytic decomposition of hydrogen peroxide in the bone repair microenvironment, reduces oxidative stress, and promotes the generation of oxygen, converting the oxidative stress microenvironment with a high active oxygen concentration into an oxygen-rich microenvironment with a low active oxygen concentration, which helps to significantly improve the microenvironment of the bone defect site, and can be used to repair bone defects, promote bone tissue repair and regeneration, and reconstruct the bioelectric microenvironment.

[0029] The preparation method of the present invention is simple, and the electrical properties and catalytic properties of the composite film can be regulated by adjusting the hydrothermal temperature, hydrothermal time, polarization field strength, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Results of EDS analysis of the cross section of the product obtained in step (1) of Example 1.

[0031] Figure 2 Results obtained by Fourier infrared testing of the hot pressing contact surface of the product obtained in step (3) of Example 1.

[0032] Figure 3 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the target product obtained in Example 1.

[0033] Figure 4 This is the EDS image of the non-hot pressing contact surface of the target product obtained in Example 1.

[0034] Figure 5A and Figure 5B They are respectively the XPS element analysis results of the non-hot pressing contact surface of the target product obtained in Example 1 and the Mn element valence state analysis results.

[0035] Figure 6 This is a SEM image of the cross section of the target product obtained in Example 1.

[0036] Figure 7 This is a SEM image of the cross section of the target product obtained in Example 1.

[0037] Figure 8 This is an AFM image of the non-hot pressing contact surface of the target product obtained in Example 1.

[0038] Fig. 9 This is the KFM diagram of the non-hot pressing contact surface of the target product obtained in Example 1.

[0039] Fig.10 is the piezoelectric coefficient d of the target products obtained in different embodiments and the final product obtained in comparative example 1 33 contrast.

[0040] Fig.11 This is the KFM diagram of the non-hot pressing contact surface of the target product obtained in Example 6.

[0041] Fig.12 This is the KFM diagram of the non-hot pressing contact surface of the final product obtained in Comparative Example 1.

[0042] Fig.13 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the target product obtained in Example 7.

[0043] Fig.14 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the target product obtained in Example 8.

[0044] Fig.15 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the target product obtained in Example 9.

[0045] Fig.16 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the target product obtained in Example 10.

[0046] Fig.17 This is a SEM image of the surface morphology of the non-hot pressing contact surface of the final product obtained in Comparative Example 2.

[0047] Fig.18 is the piezoelectric coefficient d of the target products obtained in different embodiments and the final product obtained in comparative example 3 33 contrast.

[0048] Fig.19 The UV-visible spectra of the target product obtained in Example 1 and the final product obtained in Comparative Example 2 after reacting with H2O2 at different action times and titanium sulfate, and their absorbance at 415nm.

[0049] Fig. 20 It is a dissolved oxygen curve diagram of the target product obtained in Example 1, the final product obtained in Comparative Example 1, and the final product obtained in Comparative Example 2.

[0050] Fig.21 The results are the test results of the surface potential of the non-hot pressing contact surface of the target product obtained in Example 1 under different magnetic field intensities using an AC magnetoelectric device.

[0051] Fig. 22 These are the test results of the surface potential of the non-hot pressing contact surface of the target product obtained in Example 11 at different magnetic field intensities using an AC magnetoelectric device. DETAILED DESCRIPTION

[0052] In order to better illustrate the present invention and facilitate understanding of the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0053] In the following examples and comparative examples, the reagents or instruments used without indicating the manufacturer are all conventional products available on the market. For example, the glass plate is a tempered glass plate, and polyvinylidene fluoride-trifluoroethylene (i.e., vinylidene fluoride-trifluoroethylene copolymer, Poly(vinylidene fluoride-trifluoroethylene), P(VDF-TrFE), abbreviated as PVTF) is produced by Piezotech, France, and the product model is: FC30, wherein the molar ratio of vinylidene fluoride monomer to trifluoroethylene monomer is 7:3.

[0054] Contact polarization device: It includes a high-voltage DC power supply, a copper counter electrode (consisting of a copper sheet electrode and a base copper plate electrode) and a dimethyl silicone oil tray. The output end of the high-voltage DC power supply is connected to the copper counter electrode with a wire. The membrane sample to be polarized is placed between the counter electrodes. The electric field between the counter electrodes is regulated by adjusting the output voltage. The entire device is immersed in dimethyl silicone oil to exclude water and air to avoid breakdown. The polarization device can be built by yourself or purchased commercially.

[0055] Example 1

[0056] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; a coater (height setting 0.05 mm) was used to evenly coat the mixed solution obtained above on a clean glass plate to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a TD / PVTF film.

[0057] (2) 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid were dissolved in 80 ml of deionized water and stirred for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl was 1:40, and the final concentration of potassium permanganate was 0.4 mol / L); the titanium sheet was immersed in a polytetrafluoroethylene reactor inner tank containing the above hydrothermal precursor solution, and the hydrothermal reaction was carried out at 100° C. for 10 h, and then the titanium sheet was taken out and the potassium permanganate solution remaining on the surface was washed off with deionized water to obtain a titanium sheet with a coating on the surface.

[0058] (3) The TD / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0059] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0060] Example 2

[0061] Steps (1) to (3) are the same as those in Example 1.

[0062] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 1.4 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0063] Example 3

[0064] Steps (1) to (3) are the same as those in Example 1.

[0065] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 2.1 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0066] Example 4

[0067] Steps (1) to (3) are the same as those in Example 1.

[0068] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 2.7 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0069] Example 5

[0070] Steps (1) to (3) are the same as those in Example 1.

[0071] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.7 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0072] Example 6

[0073] Steps (1) to (3) are the same as those in Example 1.

[0074] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV reverse high voltage external electric field is applied for 3 minutes to obtain the target product.

[0075] Example 7

[0076] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; a coater (height setting 0.05 mm) was used to evenly coat the mixed solution obtained above on a clean glass plate to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a TD / PVTF film.

[0077] (2) 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid were dissolved in 80 ml of deionized water and stirred for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl was 1:40, and the final concentration of potassium permanganate was 0.4 mol / L); the titanium sheet was immersed in a polytetrafluoroethylene reactor inner tank containing the above hydrothermal precursor solution, and the hydrothermal reaction was carried out at 100° C. for 12 h, and then the titanium sheet was taken out and the potassium permanganate solution remaining on the surface was washed off with deionized water to obtain a titanium sheet with a coating on the surface.

[0078] (3) The TD / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0079] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0080] Example 8

[0081] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; a coater (height setting 0.05 mm) was used to evenly coat the mixed solution obtained above on a clean glass plate to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a TD / PVTF film.

[0082] (2) Dissolve 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid in 80 ml of deionized water, and stir for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl is 1:40, and the final concentration of potassium permanganate is 0.4 mol / L); immerse the titanium sheet in a polytetrafluoroethylene reactor containing the hydrothermal precursor solution, and perform a hydrothermal reaction at 100° C. for 8 h. Then, take out the titanium sheet and wash off the potassium permanganate solution remaining on the surface with deionized water to obtain a titanium sheet with a coating on the surface.

[0083] (3) The TD / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0084] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0085] Example 9

[0086] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; a coater (height setting 0.05 mm) was used to evenly coat the mixed solution obtained above on a clean glass plate to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a TD / PVTF film.

[0087] (2) 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid were dissolved in 80 ml of deionized water and stirred for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl was 1:40, and the final concentration of potassium permanganate was 0.4 mol / L); the titanium sheet was immersed in a polytetrafluoroethylene reactor liner containing the above hydrothermal precursor solution, and the reaction was carried out at 120° C. for 10 h, and then the titanium sheet was taken out and the potassium permanganate solution remaining on the surface was washed off with deionized water to obtain a titanium sheet with a coating on the surface.

[0088] (3) The TD / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0089] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0090] Example 10

[0091] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; a coater (height setting 0.05 mm) was used to evenly coat the mixed solution obtained above on a clean glass plate to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a TD / PVTF film.

[0092] (2) 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid were dissolved in 80 ml of deionized water and stirred for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl was 1:40, and the final concentration of potassium permanganate was 0.4 mol / L); the titanium sheet was immersed in a polytetrafluoroethylene reactor inner tank containing the above hydrothermal precursor solution, and hydrothermally reacted at 90° C. for 10 h, and then the titanium sheet was taken out and the potassium permanganate solution remaining on the surface was washed off with deionized water to obtain a titanium sheet with a coating on the surface.

[0093] (3) The TD / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0094] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0095] Embodiment 11

[0096] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.05 g of cobalt tetraoxide ferrite (CoFe2O4, abbreviated as CFO) powder was added thereto, and ultrasonic dispersion was performed for 5 h, and stirring was performed for 2 h to make the CFO particles evenly dispersed in the PVTF solution to obtain a mixed solution; the mixed solution obtained above was evenly coated on a clean glass plate using a coater (height setting 0.05 mm) to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then furnace cooling to obtain a CFO / PVTF film.

[0097] (2) 0.45 g of potassium permanganate solid and 1 ml of 37% hydrochloric acid were dissolved in 80 ml of deionized water and stirred for 30 min to obtain a hydrothermal precursor solution (the molar ratio of potassium permanganate to HCl was 1:40, and the final concentration of potassium permanganate was 0.4 mol / L); the titanium sheet was immersed in a polytetrafluoroethylene reactor inner tank containing the above hydrothermal precursor solution, and the hydrothermal reaction was carried out at 100° C. for 10 h, and then the titanium sheet was taken out and the potassium permanganate solution remaining on the surface was washed off with deionized water to obtain a titanium sheet with a coating on the surface.

[0098] (3) The CFO / PVTF film obtained in step (1) is removed from the glass plate, and is placed on the titanium sheet with a surface coating obtained in step (2), and the two are combined by hot pressing to obtain a composite titanium film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0099] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0100] Example 12

[0101] Steps (1) to (3) are the same as in Example 11.

[0102] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 1.31 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0103] Example 13

[0104] Steps (1) to (3) are the same as in Example 11.

[0105] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 2.03 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0106] Embodiment 14

[0107] Steps (1) to (3) are the same as in Example 11.

[0108] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 2.53 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0109] Embodiment 15

[0110] Steps (1) to (3) are the same as in Example 11.

[0111] (4) The composite titanium film obtained in step (3) is subjected to polarization treatment: the composite titanium film is placed in silicone oil for contact polarization, and a 3.03 kV high voltage external electric field is applied for 3 minutes to obtain the target product.

[0112] Comparative Example 1

[0113] Steps (1) to (3) are the same as those in Example 1.

[0114] (4) performing polarization treatment on the composite titanium film obtained in step (3): placing the composite titanium film in silicone oil for 3 minutes without applying an external electric field to obtain a final product.

[0115] Comparative Example 2 Preparation of Ti / TD-PVTF

[0116] (1) 1 g of PVTF and 6 mL of N,N-dimethylformamide were mixed in a culture bottle to form a PVTF solution, and then 0.1 g of terbium dysprosium iron alloy (Tb-Dy-Fe alloy, abbreviated as TD) powder was added thereto, ultrasonically dispersed for 5 h, and stirred for 2 h to make the TD alloy particles evenly dispersed in the PVTF solution to obtain a mixed solution; the mixed solution obtained above was evenly coated on a clean glass plate using a coater (height setting 0.05 mm) to form a thin film on the glass plate, followed by heat treatment at 210°C for 1 h, and then cooled in the furnace to obtain a TD / PVTF film.

[0117] 2) The TD / PVTF film obtained in step (1) is removed from the glass plate, placed on a titanium sheet, and the two are combined by hot pressing to obtain a composite film, wherein the hot pressing temperature is 210° C. and the hot pressing time is 1 h.

[0118] 3) The composite film obtained in step (2) is subjected to polarization treatment: the composite film is placed in silicone oil and a 3.5 kV high voltage external electric field is applied for 3 minutes to obtain a final product.

[0119] Comparative Example 3

[0120] Steps (1) to (3) are the same as in Example 11.

[0121] (4) performing polarization treatment on the composite titanium film obtained in step (3): placing the composite titanium film in silicone oil for 3 minutes without applying an external electric field to obtain a final product.

[0122] Characterization and Identification:

[0123] In the products obtained in step (3) and step (4) of each embodiment, there are different thin films on both sides of the titanium sheet. After the MSM / PVTF film is hot-pressed into contact with the titanium sheet covered with the coating, the surface formed by the hot-pressing bonding of the MSM / PVTF film to the titanium sheet is called the hot-pressing contact surface (also called the A surface), which is relatively smooth; the other side of the titanium sheet is the surface covered with the coating, called the non-hot-pressing contact surface (also called the B surface), which is relatively matte.

[0124] The cross section of the product obtained in step (1) of Example 1 was subjected to EDS analysis. Figure 1 As shown. Figure 1 It can be seen that the product obtained in step (1) contains C, O, F, Fe, and Dy elements, that is, PVTF and TD alloy particles are uniformly present in the film. Therefore, the product obtained in step (1) is a TD / PVTF film.

[0125] The A surface of the product obtained in step (3) of Example 1 was tested by Fourier transform infrared spectrometer (ART-FTIR, Nicolet 5700) with the scanning range of the instrument being 600 to 4000 cm -1 , FTIR results are as follows Figure 2 shown. Figure 2 There are three obvious β-phase absorption peaks in the infrared spectrum: 840 cm -1 and 1285cm -1 The absorption peak at 1396 cm corresponds to the symmetric stretching vibration of CF2. -1 The absorption peak at is due to the non-planar rocking vibration of CH2, indicating that there is a β-phase PVTF film on the A side of the product obtained in step (3) of Example 1, which means that in step (3) of Example 1, the TD / PVTF film and the titanium sheet are combined during hot pressing.

[0126] The surface B of the target product obtained in Example 1 was analyzed by scanning electron microscopy and EDS. The SEM image of its surface morphology is as follows: Figure 3 As shown in the figure, it can be seen that flakes grow evenly on the surface, and the size of the flakes is between 400 and 600 nm. Figure 4 As shown, it can be seen that Ti, Mn, and O elements exist, that is, Mn and O elements exist on the surface of the Ti sheet, proving that the surface flake material contains manganese. The target product obtained in Example 1 was further analyzed by XPS, and the results are as follows Figure 5A and Figure 5BAs shown, it can be seen that: (a) it proves that there are elements such as Ti, O, and Mn on the surface of the material, and (b) according to the position and peak shape of the Mn2p double peak, the valence state of manganese is determined to be +4. Therefore, it can be determined that manganese dioxide is grown on the titanium sheet, that is, the surface material of the B surface of the target product is manganese dioxide. In summary, on the B surface of the target product obtained in Example 1, manganese dioxide nanosheets are uniformly grown on the surface.

[0127] The cross section of the target product obtained in Example 1 was subjected to scanning electron microscopy analysis. Figure 6 As shown, it can be seen that the cross section is clearly divided into two layers: the upper layer is Ti containing manganese dioxide coating, with a thickness of about 28μm; the lower layer is the TD / PVTF film bonded by heat pressing, with a thickness of about 33μm; further analysis of the upper layer of the cross section, such as Figure 7 As shown, it was found that the thickness of the manganese dioxide nanosheet coating on the titanium substrate surface was about 1.2 μm. That is, the target product obtained in Example 1 is a composite film consisting of manganese dioxide nanosheets-titanium sheets-TD / PVTF film from top to bottom.

[0128] The AFM test was performed on the B surface of the target product obtained in Example 1 using a gold-plated Si3N4 probe of NSG013 to characterize its surface morphology and roughness. The results are as follows: Figure 8 It can be seen that the surface roughness of the target product B obtained in Example 1 is about 943±195nm.

[0129] The KFM test was performed on the target product B surface obtained in Example 1 using a platinum-coated silicon probe of SCM-PIT to characterize its surface potential. The results are as follows: Fig. 9 It can be seen that the surface potential of the target product obtained in Example 1 is 541±31 mV, indicating that it is electrically active.

[0130] Using the piezoelectric coefficient measuring instrument (d 33 , ZJ-3A), a low-frequency alternating force of 0.25N and a frequency of 110Hz is applied to the surface of the piezoelectric material, and the piezoelectric coefficient d of the material is detected. 33 The piezoelectric coefficient d of the target product obtained in Examples 2 to 5 and the final product obtained in Comparative Example 1 were measured by this method. 33 The results are as follows Fig.10 As shown, it can be seen that when the polarization voltages are 0 kV, 1.4 kV, 2.1 kV, 2.7 kV and 3.7 kV, the corresponding d 33They are 0pC / N, 2.0pC / N, 4.03pC / N, 8.870pC / N, and 12.90pC / N, respectively. It can be seen that, except for Comparative Example 1, the target products obtained in each embodiment have electric potential and are electrically active; moreover, as the magnitude of the external field applied by polarization increases, the magnitude of the electric potential of the material also increases.

[0131] The target product B obtained in Example 6 was subjected to KFM test, and its image is as follows: Fig.11 As shown, the surface potential of the reverse polarized material is about -500±17 mV, which is similar to the surface potential of the target product in Example 1, but the potential direction is opposite.

[0132] The final product B obtained in Comparative Example 1 was subjected to KFM test, and its image is as follows: Fig.12 As shown, the surface potential of the unpolarized material is about 55±28 mV, indicating that it is not electrically active.

[0133] In summary, it can be seen that the potential and electrical activity of the target product obtained in each embodiment can be controlled by adjusting the magnitude of the external field strength applied by polarization.

[0134] The surface B of the target product obtained in Example 7 was analyzed by scanning electron microscopy, and its surface morphology SEM image is as follows: Fig.13 As shown, it can be seen that: on the B side of the target product, manganese dioxide nanosheets are uniformly grown on the surface, and a layer of manganese dioxide nanorods is also covered on the surface of the manganese dioxide nanosheets. The size of the nanosheets is 150 to 400 nm, and the diameter of the nanorods is 2 to 5 nm.

[0135] The surface B of the target product obtained in Example 8 was analyzed by scanning electron microscopy, and its surface morphology SEM image is as follows: Fig.14 As shown, it can be seen that on the B side of the target product, manganese dioxide nanosheets are uniformly grown on the surface, and the size of the nanosheets is 200 to 500 nm.

[0136] The surface B of the target product obtained in Example 9 was analyzed by scanning electron microscopy, and its surface morphology SEM image is as follows: Fig.15 As shown, it can be seen that: on the B side of the target product, manganese dioxide nanosheets are uniformly grown on the surface, and a layer of manganese dioxide nanorods is also covered on the surface of the manganese dioxide nanosheets. The size of the nanosheets is 500-800nm, and the diameter of the nanorods is 3-4nm.

[0137] The surface B of the target product obtained in Example 10 was analyzed by scanning electron microscopy, and its surface morphology SEM image is as follows: Fig.16 As shown, it can be seen that on the B side of the target product, manganese dioxide nanosheets are uniformly grown on the surface, and the size of the nanosheets is 100 to 400 nm.

[0138] The non-hot pressing contact surface of the final product obtained in Comparative Example 2 was analyzed by scanning electron microscopy, and its surface morphology SEM image is as follows: Fig.17 As shown, the surface of the titanium sheet is relatively flat and has no special morphology.

[0139] Using the piezoelectric coefficient measuring instrument (d 33 , ZJ-3A), a low-frequency alternating force of 0.25N and a frequency of 110Hz is applied to the surface of the piezoelectric material, and the piezoelectric coefficient d of the material is detected. 33 The piezoelectric coefficient d of the target product obtained in Examples 12 to 15 and the final product obtained in Comparative Example 3 were measured by this method. 33 The results are as follows Fig.18 As shown in the figure, it can be seen that when the polarization voltages are 0kV, 1.31kV, 2.03kV, 2.53kV and 3.03kV, the corresponding d 33 They are 0pC / N, 1.3pC / N, 7.4pC / N, 11.9pC / N, and 18.0pC / N, respectively. It can be seen that, except for Comparative Example 3, the target products obtained in each embodiment have electric potential and are electrically active; moreover, as the magnitude of the external field applied by polarization increases, the magnitude of the electric potential of the material also increases.

[0140] Performance Test:

[0141] Take a 1cm×1cm area of ​​the target product obtained in Example 1 and react it with 500μM H2O2. Samples are taken at 5min, 15min, 1h, and 5h, respectively, and the scavenging ability of different samples is detected using a hydrogen peroxide assay kit (Hydrogen Peroxide (H2O2) Content Assay Kit, Solarbio, China).

[0142] Take a 1cm×1cm area of ​​the target product obtained in Example 7 and react it with 500μM H2O2. Samples are taken at 5min, 15min, 1h, and 5h, respectively, and the scavenging ability of different samples is detected using a hydrogen peroxide assay kit (Hydrogen Peroxide (H2O2) Content Assay Kit, Solarbio, China).

[0143] Take a 1 cm × 1 cm area of ​​the final product Ti / PVTF obtained in Example 2 and react it with 500 μM H2O2. Samples are taken at 5 min, 15 min, 1 h, and 5 h, respectively, and the removal ability of different samples is detected using a hydrogen peroxide assay kit (Hydrogen Peroxide (H2O2) Content Assay Kit, Solarbio, China).

[0144] The principle is as follows: after different reaction times, the residual H2O2 in the sample reacts with the titanium sulfate in the hydrogen peroxide determination kit to produce different amounts of yellow precipitates; the resulting precipitates are dissolved to different depths and can be measured by an ultraviolet spectrophotometer at an absorbance of 415nm.

[0145] The analysis results are as follows Fig.19 shown. Fig.19 In the embodiment, when the reaction time is 5min, the surface decomposition rates of the target products obtained in Example 1 and Example 7 are close, both of which are about 13%, while the surface decomposition rate of the final product obtained in Comparative Example 1 is 5.0%; when the reaction time reaches 15min, the decomposition rate of H2O2 of the target product obtained in Example 1 is 17%, the decomposition rate of H2O2 of the target product obtained in Example 7 is 15%, and the decomposition rate of H2O2 of the final product obtained in Comparative Example 1 is 6%; when the decomposition time is 1h, the decomposition rate of H2O2 of the target product obtained in Example 1 is 57%, the decomposition rate of H2O2 of the target product obtained in Example 7 is 39%, and the decomposition rate of H2O2 of the final product obtained in Comparative Example 1 is 8%; after 5h of reaction, the decomposition rate of H2O2 of the target product obtained in Example 1 is 88%, the decomposition rate of H2O2 of the target product obtained in Example 7 is 85%, and the decomposition rate of H2O2 of the final product obtained in Comparative Example 1 is 19%.

[0146] Fig.19 The results show that compared with the Ti / TD-PVTF product without manganese dioxide coating obtained in Comparative Example 2, both the target product of Example 1 with manganese dioxide nanosheet coating and the target product of Example 7 with manganese dioxide coating of nanosheets and nanorods hybrid can significantly promote the decomposition of hydrogen peroxide, proving that the manganese dioxide nanocoating can reduce the concentration of reactive oxygen species in the oxidative stress microenvironment by decomposing H2O2 (reactive oxygen species), thereby alleviating the oxidative stress state of the microenvironment in the bone repair tissue.

[0147] The target product obtained in Example 1, the final product obtained in Comparative Example 1, and the final product obtained in Comparative Example 2 were placed in 800 μM H2O2 solution, and the dissolved oxygen concentration was detected using a dissolved oxygen meter (S9-Standard Kit JPSJ-606L, METTLERTOLEDO, China). The data was recorded every 20 seconds to obtain the dissolved oxygen curve in each solution, as shown in FIG. Fig. 20 As shown. Fig. 20It can be seen that compared with Comparative Example 2, the composite film with a manganese dioxide nanosheet coating obtained in Example 1 can produce a certain amount of oxygen through a catalytic reaction in a liquid environment containing hydrogen peroxide; compared with Comparative Example 1, the electroactive Janus film obtained in Example 1 has faster initial catalytic reaction rate and oxygen generation rate, indicating that the combined effect of manganese dioxide nanosheets and electroactivity can more quickly convert an oxidative stress environment containing active oxygen species into an oxygen-rich environment with a higher oxygen content.

[0148] The surface potential of the non-hot-pressed contact surface of the target product obtained in Example 1 was tested using an AC magnetoelectric device under different magnetic field strengths. Alternating magnetic fields with central magnetic fields of 0 Gs, 47.1 Gs and 94.2 Gs (alternating frequency of 50 Hz) were applied to the solenoid coil of the AC magnetoelectric device, and the readings of the oscilloscope connected to the non-hot-pressed contact surface of the target product obtained in Example 1 were observed and recorded. The change period of all readings was 20 ms. The results are shown in FIG. Fig.21 As shown. Fig.21 It can be seen that when the central magnetic field in the coil is 0Gs, the surface only shows weak oscilloscope noise, which is ±40mV; when the central magnetic field is 47.1Gs, the surface potential is about ±280mV; when the central magnetic field is 94.2Gs, the surface potential is about ±510mV. It can be seen that as the magnetic field strength increases, the amplitude of the change of the surface potential of the material with the magnetic field also increases, and the frequency of change is consistent with the frequency of the magnetic field alternation, which shows that the surface electroactivity of the target product obtained in Example 1 can be regulated by an external magnetic field, which means that the magnetostrictive properties of the TD alloy particles support the adjustability of the surface electroactivity of the target product obtained.

[0149] The surface potential of the non-hot-pressed contact surface of the target product obtained in Example 11 was tested using an AC magnetoelectric device under different magnetic field strengths. Alternating magnetic fields with central magnetic fields of 0 Gs, 47.1 Gs and 94.2 Gs (alternating frequency of 50 Hz) were applied to the solenoid coil of the AC magnetoelectric device, and the readings of the oscilloscope connected to the non-hot-pressed contact surface of the target product obtained in Example 11 were observed and recorded. The change period of all readings was 20 ms. The results are shown in FIG. Fig. 22 As shown. Fig. 22 It can be seen that when the central magnetic field in the coil is 0Gs, the surface only shows weak oscilloscope noise of ±37mV; when the central magnetic field is 47.1Gs, the surface potential is about ±161mV; when the central magnetic field is 94.2Gs, the surface potential is about ±357mV. It can be seen that as the magnetic field strength increases, the amplitude of the change of the surface potential of the material with the magnetic field also increases, and the frequency of change is consistent with the frequency of the magnetic field alternation, which shows that the surface electroactivity of the target product obtained in Example 11 can be regulated by an external magnetic field, which means that the magnetostrictive properties of the CFO particles support the adjustability of the surface electroactivity of the target product obtained.

[0150] In summary, the target product prepared in the above embodiments is a composite film composed of manganese dioxide nano-coating-titanium sheet (manganese dioxide nano-coating)-MSM / PVTF film, which has both manganese dioxide nano-enzyme coating surface and polarized MSM / PVTF surface, so it has both biological activity and electrical activity. On the one hand, the surface of manganese dioxide nano-coating exhibits good biological activity and obvious nano-enzyme efficient catalytic characteristics, which can catalyze the decomposition of hydrogen peroxide (H2O2) in the bone repair microenvironment, remove reactive oxygen, reduce oxidative stress, and promote the generation of oxygen, converting the oxidative stress microenvironment with high reactive oxygen concentration into an oxygen-rich microenvironment with low reactive oxygen concentration, which helps to significantly improve the microenvironment of the bone defect site; moreover, the manganese dioxide nano-coating is a mixture of nano-sheets or nano-sheets and nano-rods, with a large specific surface area and uniform morphology. After being implanted in the bone damage area, the surface of the material contacts the bone tissue microenvironment, and the larger implant surface area improves the interaction with the bone tissue microenvironment. The surface potential of the MSM / PVTF film after polarization treatment makes the composite film self-powered, which can generate electrical signals under mechanical stress, and use the electrical signals on the surface of the material to change the cell microenvironment, promote the proliferation and differentiation of bone cells, and accelerate the bone tissue repair process. At the same time, the surface electrical activity of the MSM / PVTF film after polarization treatment can also be regulated by an external magnetic field; in addition, experiments show that the surface potential provided by the MSM / PVTF film after polarization treatment promotes the catalytic activity of the manganese dioxide nanocoating and can generate oxygen more quickly. This means that when the composite film is implanted in the body as an implant, its ability to interact with the microenvironment of human bone tissue can be regulated by changing the external magnetic field, thereby improving the efficiency and quality of bone tissue regeneration, especially in the repair of osteoporotic bone damage, which can effectively improve the efficiency of bone defect repair. External field regulation greatly facilitates the regulation of implants in the body. In addition to regulating the electrical activity by an external field, composite films with different surface potentials can be obtained by changing the polarization electric field during the preparation process, or by changing parameters such as the hydrothermal temperature and the hydrothermal time to adjust the surface physicochemical properties of the composite film to obtain different biological activities and electrical activities, thereby meeting different application requirements. It can be seen that the composite film of the present invention, which reshapes the material interface microenvironment using MSM / PVTF and MnO2 nano-coatings and is applied to the surface of metal implants, has significant advantages in bone repair, not only expanding the range of interaction between the material and bone tissue, but also further promoting the repair and regeneration of bone tissue by reducing the level of oxidative stress. The composite film of the present invention can be used to repair bone defects and improve the bioelectric microenvironment. It can be used in the biomedical field as a material for reconstructing the bioelectric microenvironment of bone defects, and shows great application potential in promoting bone tissue repair and regeneration.

[0151] It can be seen that the purpose of the present invention has been completely and effectively achieved. The functional and structural principles of the present invention have been demonstrated and explained in the embodiments. Without departing from the principles, the implementation methods can be modified arbitrarily. Therefore, the present invention includes all modified implementation methods based on the spirit and scope of the claims.

Claims

1. A composite film, characterized in that: The composite is made of a titanium sheet covered with a manganese dioxide nano-coating and an MSM / PVTF film and then subjected to polarization treatment.

2. The composite film according to claim 1, characterized in that The piezoelectric coefficient d of the composite film 33 Satisfy: -23pC / N≤d 33 <0pC / N or 0pC / N<d 33 ≤23pC / N.

3. The composite film according to claim 1, characterized in that The thickness of the manganese dioxide nano coating is 1-2 μm.

4. The composite film according to claim 1, characterized in that The thickness of the MSM / PVTF film is 35-70 μm.

5. The composite film according to claim 1, characterized in that The manganese dioxide nano coating is composed of manganese dioxide nano sheets, and the size of the nano sheets is 80-900 nm.

6. The composite film according to claim 1, characterized in that The manganese dioxide nano coating is composed of manganese dioxide nano sheets and manganese dioxide nano rods. The size of the nano sheets is 80-900 nm, and the size of the nano rods is 1-4 μm.

7. The composite film according to claim 1, characterized in that The compounding is hot pressing compounding.

8. The method for preparing the composite film according to any one of claims 1 to 7, comprising the following steps: (1) preparing polyvinylidene fluoride trifluoroethylene and N,N-dimethylformamide into a polyvinylidene fluoride trifluoroethylene solution, adding a magnetostrictive material thereto, ultrasonicating for 3 to 9 hours, stirring for 2 to 4 hours, and obtaining a mixed solution; wherein the feeding ratio of the polyvinylidene fluoride trifluoroethylene, N,N-dimethylformamide and the magnetostrictive material is 1 g: (5 to 6) mL: (0.05 to 0.15) g; forming the mixed solution into a thin film by a coating method, and then heat treating at 180° C. to 240° C. for 0.5 to 2 hours, and obtaining an MSM / PVTF film after cooling; (2) dissolving potassium permanganate and HCl in a molar ratio of 1:(39-41) in deionized water, stirring for 30 min-1 h to obtain a hydrothermal precursor solution, wherein the final concentration of potassium permanganate in the hydrothermal precursor solution is 0.3-0.4 mol / L; immersing a titanium sheet in a hydrothermal reactor containing the hydrothermal precursor solution, performing a hydrothermal reaction at 80-150° C. for 5-20 h, taking out and washing with deionized water several times to obtain a titanium sheet with a manganese dioxide nano-coating on the surface; (3) hot pressing the MSM / PVTF film obtained in step (1) and the titanium sheet with a surface covered with a manganese dioxide nano-coating obtained in step (2) to obtain a composite titanium film, wherein the hot pressing temperature is 180 to 230° C. and the hot pressing time is 0.5 to 1.5 h; (4) The composite titanium film obtained in step (3) is subjected to polarization treatment to obtain the target product.

9. The method for preparing a composite film according to claim 8, characterized in that: In step (4), the high voltage electric field intensity of the polarization treatment is 40 to 70 KV / mm, and the time of the polarization treatment is 2 to 10 min.

10. Use of the composite film according to any one of claims 1 to 7, characterized in that: The composite film is used in repairing bone defects, promoting bone tissue regeneration or reconstructing a bioelectric microenvironment.